An EFL Student Case Study of the improvement of Grammar skills in a private high school -TEFL Program Portfolio - Celi Jaramillo, Karina Alexandra (2012)
The theme of this research is “An EFL student case study of the improvement of grammar skills in a private high school-TEFL Program Portfolio”. This study was carried out in the city of Loja. One student was selected for the sample. It was necessary to evaluate her knowledge in grammar because it was detected that Karen had difficulties at structuring sentences. Thus, exercises and assignments were conducted to improve her performance in grammar. An EFL student case study is a description about eight artifacts done by the student. These artifacts were applied during the four weeks of instruction and were focused on grammar skills. In the TEFL program portfolio demonstrates the correct use of the standards using assignments that were selected from the Master`s Program with the corresponding domains. Main findings were found after the analysis of grammar artifacts. Artifacts showed that grammar errors were made at the beginning but at the end of instruction student´s errors were minimal. Moreover, in the program portfolio, standards provided a significant tool for defining the language as well as the content that English language learners were expected to achieve.